2010
DOI: 10.1097/ss.0b013e3181f516ea
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Laser-Induced Breakdown Spectroscopy Spectra of Soil Samples

Abstract: Laser-induced breakdown spectroscopy (LIBS) is a rapid quantitative analytical technique that can be used to determine the elemental composition of numerous sample matrices, and it has been successfully applied in many types of samples. However, for chemically and physically complex soil samples, its quantitative analytical ability is controversial. Multivariate analytical techniques have great potential for analyzing the complex LIBS spectra. To demonstrate the feasibility of LIBS as an alternative technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…There is no doubt that the multivariate analysis is superior to univariate analysis. This has been proven by numerous researchers, for instance, the analysis of rocks [49], rare earth elements [38], glass [50], cerium oxide [51], alloy steel [52], liquid steel [53], soil [54,55], soybean oil [56], PZT (Lead Zirconate Titanate) ceramics [57], Pb in navel orange [58], Marcellus Shale [59], tailing cores [60], geologically diverse samples [49], steel melt [61], slurry [62], iron ore [63] and pellets of plant materials [64].…”
Section: The Comparison Of Calibration Methodsmentioning
confidence: 99%
“…There is no doubt that the multivariate analysis is superior to univariate analysis. This has been proven by numerous researchers, for instance, the analysis of rocks [49], rare earth elements [38], glass [50], cerium oxide [51], alloy steel [52], liquid steel [53], soil [54,55], soybean oil [56], PZT (Lead Zirconate Titanate) ceramics [57], Pb in navel orange [58], Marcellus Shale [59], tailing cores [60], geologically diverse samples [49], steel melt [61], slurry [62], iron ore [63] and pellets of plant materials [64].…”
Section: The Comparison Of Calibration Methodsmentioning
confidence: 99%
“…A number of authors [18][19][20][21][22][23] have revealed that the technique of LIBS when accompanied by the use of multivariate statistical analysis for the analysis of a large number of LIBS spectra is a very powerful tool to help us to understand the clustering of the samples into specific groups based on their chemistry. Principal component analysis (PCA) is commonly used to isolate the spectral wavelength that is a fingerprint for the presence of an element that can be correlated with chemical differences between the samples.…”
Section: Introductionmentioning
confidence: 99%
“…This is challenging because, as mentioned above 8 the quality of LIBS results obtained is enormously inuenced by the chemical and physical properties of the sample, which in turn depend on how the sample was pretreated prior to analysis. [33][34][35][36][37][38][39][40] Various methods of soil sample preparation have been developed to achieve the homogeneity required for LIBS analysis, including mechanical pressure, 41 grinding and sieving 42 and a combination of these. 39,[43][44][45] However, these potentially may be difficult to replicate in a eld setting, especially using an autonomous rover analytical platform.…”
Section: Introductionmentioning
confidence: 99%